TI_GERICHTE 12.2018.163 vom 25. Oktober 2019 , Cessione ex art. 260 LEF a più persone - legittimazione del singolo cessionario - TI Tribunale d'appello (2019)
Cessione ex art. 260 LEF a più persone - legittimazione del singolo cessionario